Soft tissue Rosai–Dorfman disease in child: A case report and literature review. Issue 29 (July 2016) - Xu, Yunlan; Han, Bingqiang; Yang, Jie; Ma, Jing; Chen, Ji; Wang, Zhigang
Abstract: Background: Rosai–Dorfman disease was commonly characterized as massive, painless, bilateral, symmetric cervical lymphadenopathy, with fever, leukocytosis, and elevated sedimentation rate. However, soft tissue Rosai–Dorfman disease (STRDD) is a rare benign tumor. Methods: We hereby present 1 case of a 17-month-old girl, an isolated subcutaneous mass was detected on her right forearm, and no signs of pain, swelling, or erythema were observed at the site. Results: The patient underwent an excisional biopsy for the mass. Immunohistochemistry results showed that it was positive for S-100 protein and CD68, whereas negative for CD1a, which supported the diagnosis of STRDD. Conclusions: The patient showed no evidence of recurrence or metastasis 2 years after the surgery. Some multifocal masses were reported to be much more prone to recurrence. Further follow-up of STRDD is necessary.